Accidental ingestion of sodium molybdate at the workplace followed by short-term biomonitoring - Bernasconi, Lucia; Brolli, Benedetta; Negro, Aurelio; Zoino, Jorge L; Schicchi, Azzurra; Petrolini, Valeria M; Lonati, Davide; Ronchi, Anna; Locatelli, Carlo A (La Medicina del Lavoro, 2022)
Introduction: Most of the molybdenum (Mo) is used in metallurgical applications, the tetrathiomolybdate form is an experimental chelating agent for Wilson’s disease. Human data of acute Mo exposure are lacking and, no report of no-observed-adverse-effect level (NOAEL) has been described until now. Case-study: We report a case of acute occupational exposure to molybdenum, with the related plasma and urine molybdenum concentrations, caused by an accidental ingestion of a sip of an anti-corrosion liquid for metal containing sodium molybdate. Our purpose was to evaluate potential systemic toxicity of molybdenum and to evaluate the dose-response/dose-effect relationship. We estimated the amount of ingested molybdenum to make a mg/kg relationship and performed repeated urine and plasma molybdenum determinations. The patient was hospitalized for three days to monitor possible development of acute symptoms/biochemical alterations. Discussion: We estimated the amount of the sip around 50 ml, with an estimation of a total of 5 gr of sodium molybdate that, for the patient bodyweight of 80 kg, would mean 62,5 mg/kg of ingested Mo. Blood and urine samples collected 2 hours after ingestion showed 50 mcg/L (reference range: 0.43 – 1.8 mcg/L) and 630 mcg/L (refence range: up to 116 mcg/L) of Mo respectively, confirming acute exposure. The patients remained asymptomatic confirming that an estimated oral dose of Mo of 62.5 mg/kg was not associated with adverse effects. Conclusions: Our value, being extrapolated by a single case, will require further confirmations from other studies to allow a full evaluation of a NOAEL. Nevertheless, it does not preclude its use in evaluating the probable absence of adverse effect in the context of acute Mo exposure.